Spin‐Dependent Electronic Structure and Magnetic Properties of 2D JANUS Mn2CFCl/CuBiP2Se6 Van Der Waals Multiferroic Heterostructures. Issue 11 (7th October 2021) - Fu, Luqian; Wang, Xiaocha; Mi, Wenbo
Abstract: 2D van der Waals (vdW) multiferroic heterostructures have potential applications in novel 2D spintronic devices. Here, the electronic structure and magnetic anisotropy of 2D vdW multiferroic Mn2 CFCl/CuBiP2 Se6 heterostructures are investigated systematically by first‐principles calculations. Ferroelectric material CuBiP2 Se6 has a built‐in electric field. Mn2 CFCl is a half‐metallicity with ferromagnetic. The plane average potential difference of Mn2 CFCl/CuBiP2 Se6 heterostructures is 0.02 eV in P↓ state and 0.39 eV in P↑ state. The magnetic anisotropy of P↑ and P↓ states is shown perpendicular magnetic anisotropy (PMA). The P↑ state exhibits metallic character with the biaxial strain of 4%, −6%, while the P↓ state demonstrates half‐metallicity at a strain of 2%, 4%, 6%. The P↑ state shows PMA at the different biaxial strain. However, the P↓ state shows PMA at biaxial strain of −2%, −4%, and 6%, which shifts PMA to in‐plane magnetic anisotropy at −6%, 2%, and 4%. These tunable electronic structure and magnetic anisotropy suggest that the 2D multiferroic Mn2 CFCl/CuBiP2 Se6 vdW heterostructures have potential applications in spintronic devices. Abstract : Total magnetic anisotropy and average planar electrostatic potential at different ferroelectric polarization directions are investigated in Mn2 CFCl/CuBiP2 Se6 multiferroic heterostructures. It is found that the potential difference can be tailored by the ferroelectric polarization of CuBiP2 Se6 . The heterostructures show the perpendicular magnetic anisotropy at different ferroelectric polarization directions. Meanwhile, the magnetic anisotropy can also be tailored by biaxial strains.